La responsabilidad civil objetiva por uso indebido de tarjetas de crédito y débito - Borja Arias, Willan Santiago (2023)
ABSTRACT: The primary objective of this research work is to determine who should assume the risk and responsibility, to focus on where the losses caused by the theft of the stored resources in the account are located, because the holder of the credit card, debit card or the account holder does not approve such operation. One way to simplify the goal of this investigation is to focus on the question of who is breaching contractual obligations in the event of an irregular withdrawal of funds from a bank account when a debit card is used as an access code. and/or the keys that accompany it. In the first unit, the concepts, characteristics, procedures and everything related to the regulations related to the responsibilities of people for their wrong use of credit and debit cards will be addressed. In the second unit, the different types of credit card fraud, subject prevention obligations, prevention of fraudulent use by the user, by the issuing entity and by the participating establishment will be analysed. In the third unit I will discuss liability for improper use by a third party in the event of: forgery of the credit card, loss or theft of the credit card, fraudulent use of the credit card by third parties. authorized and contractual liability based on strict liability criteria. With the results obtained, the existing problems based on the misuse of credit and debit cards will be evident, and their consequences will also be considered to obtain a specific conclusion from the study carried out in this degree work